Research-creation in the context of doctoral training in design and creation in Colombia - Silva-Cañaveral, Sandra Johana (Universidad Pedagógica y Tecnológica de Colombia, 2016)
I propose a reflection about how a creator does research in the field of visual arts, based on an experience derived from my own investigative and creative path during the doctoral pursuit, and in contrast with my experience in creative processes as a professional artist. Among the transformations that are in play today, also there is the willing to give back the meaning to the concept of knowledge, which would be interwoven to what we are. Knowledge would mean, first of all but not exclusively, a self-awareness, a self-transforming experience that in one way or another can make us "wiser" (more prudent, in the sense of the Aristotelian phronesis). In that sense, perhaps it could be said that to be a Doctor should not only mean to master the methods of the anonymous enterprise that is science; but also, and especially, it means to accomplish a self-transformative experience. To become a Doctor should also mean to reach a certain kind of virtue, to have been transformed from a certain kind of person into a better one.